Optimization of a formulation of dry sweet butifarra made with LLama meat, pecans and kañiwa - Salvá Ruiz, Bettit Karim (2021)
In the formulation of dried sweet sausage, pork meat and fat are traditionally used, which can be replaced by healthy products such as pecans (Carya illinoinensis) and kañiwa (Chenopodium pallidicaule); as well as llama meat (Lama glama) that is low in fat and cholesterol. For this reason, the present investigation aimed to optimize a formulation of dried sweet sausage considering three main components: llama meat, kañiwa flour and pecans. The D-Optimal mixture design method of the Design-Expert®7 program was applied, obtaining fourteen formulations. For each formulation, color, water activity and texture profile were evaluated. Only the cohesiveness fit a meaningful mathematical model. Subsequently, the optimization of the variable response was carried out, using the desirability function of the "objective value" type, so that the product could resemble the target (sausage made with pork meat and fat). In the sensory analysis of the optimal formulation, four sensory attributes were evaluated: color, odor, taste and texture, in a Z test to demonstrate whether the sample mean of the degree of satisfaction for each attribute of the product was acceptable or not. All these attributes are believed to be above the population mean taken as a target. In conclusion, the optimal formula was composed of 80% llama meat and 20% pecans, observing that kañiwa flour did not improve the texture and color of the sausage.